In memory of Peter K. Smith: sparking a global research community with impactful bullying research - Strohmeier, Dagmar; Toda, Yuichi; Salmivalli, Christina (Informa UK Limited, 2026)
We are very sorry to announce that Peter K. Smith, Emeritus Professor of Psychology and William Thierry Preyer awardee for Excellence in Research on Human Development of the European Association of Developmental Psychology passed away after a short but severe illness. Peter was an outstanding developmental psychologist with a special interest in children's social development, especially on children's play. His most extensive research has been on bullying and violence in schools where he also led a large number of research projects. Peter's research was characterized by his mission in building strong international research communities. Peter helped many researchers around the globe in setting up their own research agenda on school bullying including evidence-based interventions. Peter's professional career was not only characterized by highly impactful scientific achievements, but also by his kindness, generosity, generativity and great sense of humour. Peter was active in connecting and educating researchers until his sudden illness and transfer to the hospital some months ago. His ability to spark a global research community leaves a strong legacy.